Innovative oriented development of the social sphere of the regional ecosystem’ scientific and production cluster - Malakhovskyi, Y.; Levchenko, O.; Nabulsi, Hussein; Малаховський, Ю. В.; Левченко, О. М.; Набульсі, Хусcейн (My University, 2020)
The purpose of the publication is to determine the prospects of innovatively oriented development of the social sphere of scientific and production clusters of regional ecosystems with the preferential use of public-private partnership tools. It is concluded that еhe modern method of managing the development of the social sphere is the state innovation regulation of public management of public-private partnership with the use of e-Government facilities; management of virtual networks; fundraising; outsourcing; creation of social technology platforms; crowdfunding; meeting the needs of stakeholders in obtaining high-tech social services; the formation of educational production clusters, “nodes” of stabilization and development, technical, intellectual, information, social “centers of excellence”; top-priority designing on the periphery of forward-looking, innovative and technology-intensive technologies.
Keywords: innovation; innovative oriented development; social sphere; scientific and production cluste; regional ecosystem; public-private partnership